g(x)=x+7(2x)2x+14

Simple and best practice solution for g(x)=x+7(2x)2x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(x)=x+7(2x)2x+14 equation:


Simplifying
g(x) = x + 7(2x) * 2x + 14

Multiply g * x
gx = x + 7(2x) * 2x + 14

Remove parenthesis around (2x)
gx = x + 7 * 2x * 2x + 14

Reorder the terms for easier multiplication:
gx = x + 7 * 2 * 2x * x + 14

Multiply 7 * 2
gx = x + 14 * 2x * x + 14

Multiply 14 * 2
gx = x + 28x * x + 14

Multiply x * x
gx = x + 28x2 + 14

Reorder the terms:
gx = 14 + x + 28x2

Solving
gx = 14 + x + 28x2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by 'x'.
g = 14x-1 + 1 + 28x

Simplifying
g = 14x-1 + 1 + 28x

Reorder the terms:
g = 1 + 14x-1 + 28x

See similar equations:

| 11/18x^2-7x-56=0 | | 0.6111x^2-7x-56=0 | | 4(x+2)=3(2x-(6-x)) | | 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x | | 2x+x=59 | | 35+x+2x=42+9x | | 50-8x-3=15 | | 50-8x-3=16 | | 50-8x-3=18 | | 50-8x-4=18 | | 50-8x-5=18 | | 50-8x-6=18 | | 50-8x-12=18 |

Equations solver categories